International external quality assurance of JAK2 V617F quantification - Asp, Julia (Ann Hematol, 2018)
External quality assurance (EQA) programs are vital to ensure high quality and standardized results in molecular diagnostics. It is important that EQA for quantitative analysis takes into account the variation in methodology. Results cannot be expected to be more accurate than limits of the technology used, and it is essential to recognize factors causing substantial outlier results. The present study aimed to identify parameters of specific importance for JAK2 V617F quantification by quantitative PCR, using different starting materials, assays, and technical platforms. Sixteen samples were issued to participating laboratories in two EQA rounds. In the first round, 19 laboratories from 11 European countries analyzing JAK2 V617F as part of their routine diagnostics returned results from in-house assays. In the second round, 25 laboratories from 17 countries participated. Despite variations in starting material, assay set-up and instrumentation the laboratories were generally well aligned in the EQA program. However, EQA based on a single technology appears to be a valuable tool to achieve standardization of the quantification of JAK2 V617F allelic burden.